DNA typing from fluorescent powder dusted latent fingerprints - Chatchadaporn Thamnurak (2018)
DNA profiles were successfully typed from four latent fingerprints deposited on glass plate, glossy magazine paper, and plastic surface that were dusted with red, green, and yellow fluorescent powder. No or partial DNA profile was generated from one latent fingerprint samples. In addition, two DNA extraction methods, i.e., QIAamp ® DNA Mini Kit and Chelex ® 100 were compared. Experiments demonstrated that the absorbance measurements by spectrophotometery were interfered by colors of the fluorescent powder extracts, although these did not affect DNA profiling and detection of the PCR-amplified products by the genetic analyzer instrument. Results demonstrated that QIAamp ® DNA Mini Kit was more suitable than Chelex ® 100 for recovery of DNA from fluorescent powder dusted fingerprints. The quality of partial DNA profiles obtained from fluorescent powder dusted fingerprints was improved through the application of low copy number (LCN) typing, by increasing the number of PCR cycles from 28 to 34. Surface type had an effect on the number of loci obtained, and fluorescent fingerprint powders used had subtle effect on the profile quality obtained. © 2011 Elsevier Ireland Ltd.